Analisis Efektifitas Sistem Jaminan Kuantitas Minyak dan Gas Bumi dalam rangka Peningkatan Keandalan Informasi Keuangan kepada SKK Migas berdasarkan COSO Framework: Studi Kasus pada Kontraktor Kontrak Kerja Sama - Dameria Hutapea; Ludovicus Sensi Wondabio (Politeknik Ganesha Medan, 2025)
This research aims to answer the phenomenon of the implementation of the Oil and Gas Quantity Assurance System on the Cooperation Contractor (KKKS) to provide certainty that the production and lifting figures presented in the Financial Quarterly Report (FQR) can be traced (trace-able) and examined (audit-able) by analyzing the effectiveness of the oil and gas quantity assurance system in order to increase the reliability of financial information to SKK Migas based on the COSO Framework. This research uses a strategy in the form of a case study (single case study) using a single unit of analysis. Data obtained from semi-structured interviews, observations, company documents. This research uses qualitative descriptive analysis. The results on the analysis of the effectiveness of the quantity assurance system based on the COSO Internal Control - Integrated Framework have fulfilled the indicators that have been determined on the 5 components of COSO (Control Environment, Risk Assessment, Control Activity, Information and Communication & Monitoring Activity), as follows, the company already has a code of conduct and the existence of an ethics committee formed, then from top management has also determined the company's objectives both the Company's objectives in general and the objectives for the implementation of this quantity assurance system and have been communicated to all employees of the company, coupled with the development of infrastructure through the technology system used as a control tool, and all matters related to policies and procedures are well documented and have been communicated to all company employees either by email or letter of interoffice-correspondence, then monitoring activities on this quantity assurance system have also been included in the jobdesc in accordance with the principle of continuous improvement. The implementation of the quantity assurance system based on the 5 components of the COSO Framework has fulfilled the indicators that have been determined but based on the results of the interview with the personel internal company for the next implementation of the quantity assurance system, it is necessary to separate between executor and assessor to maintain segregation of duties.